2022
DOI: 10.3390/cancers14071622
|View full text |Cite
|
Sign up to set email alerts
|

Does Inflammation Contribute to Cancer Incidence and Mortality during Aging? A Conceptual Review

Abstract: Aging is associated with chronic low-grade inflammation, cancer incidence and mortality. As inflammation contributes to cancer initiation and progression, one could hypothesize that age-associated chronic low-grade inflammation contributes to the increase in cancer incidence and/or mortality observed during aging. Here, we review the evidence supporting this hypothesis: (1) epidemiological associations between biomarkers of systemic inflammation and cancer incidence and mortality in older people, (2) therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 92 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…Inflammation is a known risk factor for cardiovascular disease and has been implicated in the pathogenesis of MI. Therefore, a weaker inflammatory response to pneumonia could result in a lower risk of MI in these patients [ 26 , 27 ]. Secondly, patients with these underlying conditions may have a higher prevalence of comorbidities that are protective against MI.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a known risk factor for cardiovascular disease and has been implicated in the pathogenesis of MI. Therefore, a weaker inflammatory response to pneumonia could result in a lower risk of MI in these patients [ 26 , 27 ]. Secondly, patients with these underlying conditions may have a higher prevalence of comorbidities that are protective against MI.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired endothelial function is thought to contribute to the increased cardiovascular risk ( Craighead et al, 2020 ), vascular aging associated with atherosclerotic ischemic stroke ( Koutsaliaris et al, 2022 ), and oxidative stress–inflammation in chronic kidney disease ( Ebert et al, 2021 ). Aging is associated with chronic low-grade inflammation, cancer incidence, and mortality ( Guerville et al, 2022 ), a physiological process mediated by numerous biological and genetic pathways, which are a driving force for all age-related diseases ( Li et al, 2021 ). Cancer often arises in the context of an altered tissue microenvironment landscape ( Laconi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 25 Inflammation contributes to carcinogenesis through several stages, particularly reactive oxygen species produced by activated inflammatory cells, which could promote genomic instability/DNA mutations. 26 Considering its rapid, widely available, and relatively inexpensive assessment through routine blood count analysis, NLR in peripheral blood is being increasingly studied as a systemic inflammatory marker. 27 Our study showed NLR was elevated in LC compared with HC, while no significant difference was found between LC and cirrhotic HCC.…”
Section: Discussionmentioning
confidence: 99%